Effect of Private Investment and Exchange Rate on Rice Output in Nigeria: A Bivariate Analysis - Henrietta, Udeme; Nwalem, Monday Patrick (Kwaghe International Journal of Sciences and Technology, 2024)
Studying the effects of exchange rate fluctuations on crop output can provide valuable insights into the relationship between exchange rates and agricultural performance. This research focused on how private investment and exchange rates specifically impact rice production. The study employed a Vector Error Correction Model (VECM), Impulse Response, and Variance Decomposition to achieve its objectives. The findings revealed that both foreign direct investment (FDI) and gross domestic private investment significantly affect rice output. Additionally, exchange rates and labor also have a significant impact on rice production. The analysis showed that rice output responds negatively to a unit shock in exchange rates and similarly negative responses to shocks in FDI, gross domestic investment, and labor. The study concluded that FDI, gross domestic investment, exchange rates, and labor contributed to rice output during the examined period. To attract foreign partners and enhance agricultural output, the study suggests implementing tax incentives and improving security. Furthermore, re-eval_uating the exchange rate could encourage the importation of agrochemicals, genetically modified seeds, farming equipment, and other inputs, thereby boosting the agricultural subsector. These policies would influence production incentives and, consequently, the allocation of resources across sectors.